Complete mitogenomes of Anopheles peditaeniatus and Anopheles nitidus and phylogenetic relationships within the genus Anopheles inferred from mitogenomes - Jing Guo; Zhen-Tian Yan; Wen-Bo Fu; Huan Yuan; Xu-Dong Li; Bin Chen (Parasites & Vectors, 2021)
Abstract Background Despite the medical importance of mosquitoes of the genus Anopheles in the transmission of malaria and other human diseases, its phylogenetic relationships are not settled, and the characteristics of mitochondrial genome (mitogenome) are not thoroughly understood. Methods The present study sequenced and analyzed the complete mitogenomes of An. peditaeniatus and An. nitidus, investigated genome characteristics, and inferred the phylogenetic relationships of 76 Anopheles spp. Results The complete mitogenomes of An. peditaeniatus and An. nitidus are 15,416 and 15,418 bp long, respectively, and both include 13 PCGs, 22 tRNAs, two tRNAs and one control region (CR). Mitogenomes of Anopheles spp. are similar to those of other insects in general characteristics; however, the trnR and trnA have been reversed to “trnR-trnA,” as has been reported in other mosquito genera. Genome variations mainly occur in CR length (493–886 bp) with six repeat unit types identified for the first time that demonstrate an evolutionary signal. The subgenera Lophopodomyia, Stethomyia, Kerteszia, Nyssorhynchus, Anopheles and Cellia are inferred to be monophyletic, and the phylogenetic analyses support a new phylogenetic relationship among the six subgenera investigated, in that subgenus Lophopodomyia is the sister to all other five subgenera, and the remaining five subgenera are divided into two clades, one of which is a sister-taxon subgenera Stethomyia + Kerteszia, and the other consists of subgenus Nyssorhynchus as the sister to a sister-group subgenera Anopheles + Cellia. Four series (Neomyzomyia, Pyretophorus, Neocellia and Myzomyia) of the subgenus Cellia, and two series (Arribalzagia and Myzorhynchus) of the subgenus Anopheles were found to be monophyletic, whereas three sections (Myzorhynchella, Argyritarsis and Albimanus) and their subdivisions of the subgenus Nyssorhynchus were polyphyletic or paraphyletic. Conclusions The study comprehensively uncovered the characteristics of mitogenome and the phylogenetics based on mitogenomes in the genus Anopheles, and provided information for further study on the mitogenomes, phylogenetics and taxonomic revision of the genus. Graphical abstract